Investigation of growth stimulating activity of 2-heteryl-[1,2,4]triazolo [1,5-c]quinazolines and products of its nucleophilic degradation - Bilyi, A. K.; Kovalenko, S. I.; Prihodko, O. V. (Zaporozhye Medical Journal, 2013)
Nucleophilic degradation of 2-heteryl-[1,2,4]triazolo[1,5-c]quinazolines was investigated and the structure of 2-(3-heteryl)-1H-1,2,4-triazol-5-yl]phenylamines was unequivocally proved by spectral methods. Growth stimulating activity of these compounds was investigated and it was found that the most pronounced growth stimulating activity 2.5 and 2.7 compounds showed among studied ones. They contain benzofuran and indole radicals correspondingly in position 2 of triazole ring.